DOSIMETRI BORON NEUTRON CAPTURE THERAPY DENGAN VARIASI PROYEKSI PADA TRANSVERSE COLON CANCER (TCC) MENGGUNAKAN PHITS - Putri, Sarika Setya; Sardjono, Yohanes; Irwan, Mochammad Rafli (Universitas Nusa Cendana, 2025)
Transverse Colon Cancer (TCC) is a type of cancer that attacks one of the pars of Colon, patients with TCC clinically have a low quality of life due to the risks caused. So that optimal treatment is needed that is able to stop the metastasis of cancer cells, but has minimal side effects on other tissues. BNCT (Boron Neutron Capture Therapy) treatment with the selective targeting method is claimed to be able to provide high patient justification, but the most optimal projection is needed to ensure an effective dose distribution in cancer cells. In this case the collimator should be kept as close as possible, since the thermal neutron fluxs greatly decreases as the distance from the collimator increases. The evaluation of BNCT planning treatment was carried out computationally using the Particle and Heavy Ion Code Transport System (PHITS) version 3.30, to determine the dosymmetry of the abdominal phantom voxel, which was varied into four projections, namely LLD AP (Left Lateral Decubitus Antero-Posterior), LLD PA (Left Lateral Decubitus Postero-Anterior), Lateral Dextra and Lateral Sinistra. Based on the results of simulation and evaluation, it is confirmed that the dose and irradiation time examined in the transverse colon are significantly reduced in the projection of LLD AP is more effectively applied to TCC.